Make yourself a teacher : rabbinic tales of mentors and disciples - Handelman, Susan A. (Samuel and Althea Stroum lectures in Jewish studies., 2011)
Make Yourself a Teacher is a teaching book and a book about teaching. It discusses three dramatic, well-known stories about the student and teacher Rabbi Eliezer ben Hyrcanus from the Oral Torah. The stories of R. Eliezer serve as teaching texts and models for reflection on the teacher/student relationship in the Jewish tradition and in contemporary culture, with special emphasis on the hevruta mode of Jewish learning, a collaborative process that invites the reader into a dialogue with teachers past and present. Susan Handelman considers how teacher/student relations sustain and renew the Jewish tradition, especially during troubled times. In her commentary on historical and contemporary educational practices, she asks a range of questions about teaching and learning: What is it that teachers do when they teach? How do knowledge, spirituality, and education relate? What might Jewish models of study and commentary say about how we teach and learn today? Handelman not only presents pedagogical issues that remain controversial in today's debates on education but she also brings the stories themselves to life. Through her readings, the stories beckon us to sit among the sages and be their students. -- from back cover.